Study of tricho-compost and rice husk biochar applications to development of Phytophthora late blight diseases and yields of potato plants. Issue 1 (February 2020) - Meilin, A; Rubiana, R; Hendri, J; Primilestari, S; Handoko, S; Rustam,
Abstract: Increasing crop productivity can do through improved cultivation technology by utilizing agricultural waste. This study aims to determine the development of Phytophthoralate blight deseases and yields of potato crops through the applications of tricho-compost and rice husk biochar. Trico-compost and biocharapplication on agriculture has benefits to improving soil quality, enhance crop yield, also reduce carbon and mitigate green house gas emission. Potato varieties used are Granola. Beds covered with plastic mulch, fertilizing using NPK according to recommendations, weeding weeds according to conditions, controlling pests and diseases based on Integrated Pest Control. The difference in technological treatment studied was 1) tricho-compost 10 tons/ha, 2) tricho-compost 10 tons/ha + rice husk biochar 1 ton/ha, 3) tricho-compost 10 tons/ha + rice husk biochar 2 tons/ha, and control(farmer technology without tricho-compost and without rice husk biochar). The environmental design used was a Randomized Block Design (RBD) with 7 replications. Data were analyzed by The F test and further tests used with Duncan. Results showed that the intensity of Phytophthoraleaf deseaseswas lower in potato fields with tricho-compost and rice husk biochar applications. Application of tricho-compost + rice husk biochar 2 tons/ha can increase potato productivity to 27 tons/ha (28.6% higher than farmer technology), and improve the quality of potato tubers, especially XL tubers.